2013
DOI: 10.1007/s10661-013-3514-7
|View full text |Cite
|
Sign up to set email alerts
|

Land use impact on soil quality in eastern Himalayan region of India

Abstract: Quantitative assessment of soil quality is required to determine the sustainability of land uses in terms of environmental quality and plant productivity. Our objective was to identify the most appropriate soil quality indicators and to evaluate the impact of six most prevalent land use types (natural forestland, cultivated lowland, cultivated upland terrace, shifting cultivation, plantation land, and grassland) on soil quality in eastern Himalayan region of India. We collected 120 soil samples (20 cm depth) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 18 publications
5
30
0
4
Order By: Relevance
“…Similar results were obtained in many previous studies on this subject (Alem and Pavlis, 2014;Binkley and Fisher, 2013;Singh et al, 2014). For that reason, planners have to construct an implementation method in accordance with public demands and quality of resources.…”
Section: Rasprava I Zaključaksupporting
confidence: 84%
“…Similar results were obtained in many previous studies on this subject (Alem and Pavlis, 2014;Binkley and Fisher, 2013;Singh et al, 2014). For that reason, planners have to construct an implementation method in accordance with public demands and quality of resources.…”
Section: Rasprava I Zaključaksupporting
confidence: 84%
“…Soil properties that are widely acknowledged as good indicators of soil quality, but with factor loading scores ≤ 0.70, were also retained. Soil physical, chemical, and biological properties that have been suggested as important soil quality indicators include soil organic carbon, available nutrients and particle size, BD, pH, soil aggregate stability, CEC, and available water content (Doran and Parkin, 1994;Larson and Pierce, 1994;Karlen et al, 1997;Zornoza et al, 2007Zornoza et al, , 2015García-Ruiz et al, 2008;Qi et al, 2009;Marzaioli et al, 2010;Fernandes et al, 2011;Lima et al, 2013;Merrill et al, 2013;Rousseau et al, 2012Rousseau et al, , 2013Singh et al, 2014). In cases in which more than one soil property was found to be of high importance under a single PC, Pearson's correlation coefficients were used to determine if any of these variables are redundant (Qi et al, 2009).…”
Section: Statistical Analyses and Index Developmentmentioning
confidence: 99%
“…SQ was greatest under native, perennial vegetation, and declined with increasing levels of soil disturbance resulting from cultivation. Singh et al (2014) selected indicators from a data set of 29 soil properties by PCA and produced an SQI which indicated that SQ in the natural forest land and grasslands was higher than in the cultivated sites. Interestingly, these authors highlighted that SOC and exchangeable Al were the two most powerful indicators of SQ in the eastern Himalayan region of India.…”
Section: Land Use Changes and Soil Qualitymentioning
confidence: 99%